Optimizing Postcardiac Transplantation Outcomes in Children with Ventricular Assist Devices: How Long Should the Bridge Be?. Issue 7 (July 2020) - Riggs, Kyle W.; Zafar, Farhan; Lorts, Angela; Villa, Chet R.; Bryant, Roosevelt; Morales, David L.S.
Abstract : Ventricular assist devices (VADs) decrease waitlist mortality and improve end-organ function. Therefore, we sought to determine the duration of VAD support that could allow for optimal posttransplant outcomes. Pediatric transplant recipients were identified from the United Network for Organ Sharing database. Inflection points were determined using hazard of mortality associated with support time fitted by cubic spline method. Of 685 patients, those supported for >2 months had a significant decrease in inotrope use and mechanical ventilation and an increase in functional status compared with those supported for <2 months (all p < 0.001). Those supported for 2–4 months experienced better posttransplant survival than <2 months ( p = 0.031). In durable pulsatile devices, similar improvement was seen in mechanical ventilation and functional status for the 2–4 month group with superior survival compared with <2 months ( p = 0.008) and >4 months ( p = 0.012). In continuous flow devices, used in patients overall less ill, the inflection point was >3 weeks with improvement in most end-organ function ( p < 0.001) and posttransplant survival ( p = 0.014) compared with <3 weeks. In general, a period of VAD support is associated with improvement in pretransplant risk factors and better posttransplant survival. This suggests that most patients bridged to transplantation by VADs should be supported for some time before listing to optimize posttransplant outcomes. Abstract : Supplemental Digital Content is available in the text.